Quantificação de poluentes emitidos durante a queima de biomassa florestal em laboratório - Amaral, Simone Simões [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Various pollutants are released into the atmosphere through the burning of forest biomass. Identify and quantify emissions of these compounds is of fundamental importance to the understanding of its effects. Thus, this work aims to quantify the main pollutants emitted during the burning of the forest biomass of the Amazon and Araucaria. Gas concentrations (CO2, CO, NOx) and particulate matter smaller than 2.5 μm (PM2.5) were quantified. The behavior of temperature, burning rate, modified combustion efficiency (MCE) and emission factor (EF) along the burning of biomass also were evaluated. Concentration and diameter values of particulate matter were discussed regarding the stages of combustion (flame and smoldering). The biomasses were characterized chemically, in order to evaluate possible relationships between their composition and the emission of pollutants. Approximately 2 kg each biomass was burned, whose moisture content was around 12 %. PM2.5 sampling was made using two equipment (DataRam4 and Cascade Impactor), already in gaseous sampling was used a continuous analyzer specific (Rosemount Analytical). The biomass of Araucaria showed the higher lignin content (35%) and higher CO2 emission factor (1,708.30 ± 127.91 g/kg), when compared to the biomass of the Amazon, whose CO2 EF was 1,581 ± 28.88 g/kg. Higher EF CO was obtained on burning in the Amazon biomass (48.61 ± 6.74 g/kg). The CO2 emission factor and CO appeared to be influenced by the lignin content of biomass. The biomass of Araucaria issued higher particles and in higher concentrations when compared to the biomass of the Amazon. Positive correlations were observed between the EF PM2.5 and CO2 with the ECM

Diversos poluentes são liberados para a atmosfera mediante a queima de biomassa florestal. Identificar e quantificar as emissões destes compostos é de fundamental importância para a compreensão dos seus efeitos. Assim, este trabalho visa quantificar os principais poluentes emitidos durante a queima das biomassas florestais da Amazônia e de Araucária. Foram determinadas as concentrações gasosas (CO2, CO, NOx) e de material particulado menor que 2,5 μm (PM2,5). Avaliaram-se também o comportamento da temperatura, taxa de queima, eficiência de combustão modificada (ECM) e fator de emissão (FE) ao longo da queima das biomassas. Valores de concentração e diâmetro de material particulado foram discutidos quanto às fases de combustão (chama e incandescência). As biomassas foram caracterizadas quimicamente, com intuito de avaliar possíveis relações entre sua composição e a emissão de poluentes. Foram queimados aproximadamente 2 kg de cada biomassa, cujo teor de umidade estava em torno de 12%. A amostragem de PM2,5 foi feita utilizando dois equipamentos (DataRam4 e Impactador de Cascata), já na amostragem gasosa utilizou-se um analisador contínuo específico (Rosemount Analytical). A biomassa de Araucária apresentou maior teor de lignina (35 %) e fator de emissão de CO2 mais elevado (1.708,30±127,91 g/kg), quando comparado à biomassa da Amazônia, cujo FE de CO2 foi de 1.581±28,88 g/kg. Maior FE de CO foi obtido na queima da biomassa da Amazônia (48,61±6,74 g/kg). O fator de emissão de CO2 e CO pareceram ser influenciados pelo teor de lignina da biomassa. A biomassa de Araucária emitiu partículas maiores e em maior concentração quando comparado à biomassa da Amazônia. Observaram-se correlações positivas entre os FE de CO2 e PM2,5 com a ECM
Keywords: Biomassa; Combustão; Gases de combustão; Combustão - Medição; Biomass